Economics Ethics in the Fatwa of Islamic Economics - Muhammad Maksum (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2015)
The fatwa by the National Sharia Board (Dewan Syariah Nasional/DSN) of Indonesian Ulema Council (Majlis Ulama Indonesia/MUI) and The Sharia Advisory Council of Central Bank of Malaysia/Bank Negara Malaysia (BNM) on Islamic economics is dominated by its ethical aspects. The prohibition of riba (interest), for instance, is an Islamic ethic which is mostly set in both institutions. In this case, the Legal consideration contains more ethics than fatwa verdicts. The ethics in the legal consideration is commonly based on the basic ethical principles of The Noble Qur'an, the hadith and the Islamic jurisprudence. In the meantime, the ethics for the object of contract in DSN is mentioned more in the fatwa verdict than in their legal consideration while the ethics for contract performer is equally found in both areas. This thesis is discovered by reading the DSN's fatwa from 2000 t0 2010 and the MPA's fatwa from 1997 to 2010. Once identified, the ethics in both institutions is classified into a particular category. As the result, this research generates a great implication on the dominant aspect of Islamic ethics in its legal formal.